EFL teachers’ beliefs towards current methods of teaching English grammar in a selected language centre / Mozhgan Azimi - Mozhgan, Azimi (2016)

(untitled)
The purpose of this qualitative descriptive study was to explore the language teachers’ beliefs about teaching and learning English grammar. In addition, this study compared the teachers’ beliefs and their actual behaviors in the class. The “Action Theory” (Argyris & Schön, 1984) was chosen regarding this issue. Furthermore, this study investigated whether or not there was any compatibility between the teachers’ beliefs and practice and if the participants were aware of it or not. This paper tried to investigate Iranian language teachers’ beliefs about the methods/techniques used in the class. That is, this study examined and described the current methods of English grammar teaching. The present study is a case study done in a semi-government language center in Mashhad, Iran. Three female language teachers were selected as samples (cases) for collecting qualitative data for answering the research questions. The teachers were selected purposefully (case study) and non-randomly. They were Iranian, female and non-native speakers of English from the same L1 background (Persian). To identify the language teachers’ beliefs about teaching and learning English grammar, a series of observations was done. Some interviews with subjects were conducted to make known their beliefs regarding teaching and learning English grammar. The Constant Comparative Method (CCM) was used to analyze the data obtained from observations and interviews. The findings of this study revealed that sometimes there was no compatibility between teachers’ beliefs and their actual behaviours in the classroom. In most cases, teachers were not aware of this incompatibility. The results suggested that language teachers believed that teaching grammar was boring and was not useful, hence they underestimated it. This study also revealed the importance of using native language in the EFL class.